The white mans burden: why the wests efforts to aid the rest have done so much ill and so little good - Easterly, Willian (New York: The Penguin Press, 2006)
Contents: Why planners cannot bring prosperity,the legend of the big push,you cant plan a market,planners and gangters,the rich have markets the poor have bureaucrats,bailing out the poor,the healers triumph and tragedy,from colonialism to postmodern imperialism,invading the poor,homegrown development,the future of western assistance.
Include appendix
Keywords: Asistencia extranjera - Economía